A performance evaluation of electromagnetic time reversal method for locating faults in branched cable networks - Junior, Pedro Da Costa [UNESP]; De Souza, Andre Nunes [UNESP]; Martins, Andre Christovao Pio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2019)
The post-failure impedance estimative method is one of the most used ways to locate faults in distribution systems. However, the presence of the distributed generation can degrade the precision of this kind of procedure. To get superior quality results, one can do the analysis using the electromagnetic transients of current or voltage since they are less affected by the presence of distributed generation. The electromagnetic time reversal method is more used in non-homogeneous environments to emphasize a wave at a point with excellent precision and locate sources that produce perturbations in a specific domain. The basic idea of the electromagnetic time reversal is to use the property of time reversibility of the wave equation. This property allows a reversion in the time domain of the transients, observed in strategic points of the system, to evidence the location of the related electromagnetic energy. This work presents an evaluation of the electromagnetic time reversal method (EMTR) for locating faults in underground distribution networks. This paper revised the time reversal method, and investigate its application in a virtual branched underground distribution system.
Keywords: Electromagnetic time reversal; EMTR; Fault location; Power distribution faults; Power system transients